2020
DOI: 10.1021/acs.iecr.0c01585
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Plasma Fischer–Tropsch Synthesis Using Hierarchically Connected Porous Co/SiO2 Catalysts Prepared by Microwave-Induced Co-assembly

Abstract: Catalytic plasma-enhanced Fischer–Tropsch synthesis (FTS) for gas-to-liquid conversion was investigated using a recently developed novel nanostructured, hierarchically connected micro/meso-porous Co/SiO2 catalyst obtained through microwave irradiation-induced coassembly of the catalyst and catalyst support precursors (Catalysts202010152). This catalyst structure with its micron-scale morphological and chemical heterogeneity is particularly suitable for catalytic plasma reactions. It is shown that a dielectric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 80 publications
(232 reference statements)
1
26
0
Order By: Relevance
“…22 Akay et al showed DBD coupled with Co/SiO 2 for Fischer−Tropsch synthesis. 23 In both cases, reactant conversions with plasma−catalyst combinations are higher than those with plasma alone or catalyst alone under tested conditions. Song et al placed DBD coupled with HZSM-5 downstream of polyethylene pyrolysis volatiles to generate aromatics-enriched oil and showed product yields are sensitive to plasma conditions.…”
Section: ■ Plasma Characterizationmentioning
confidence: 93%
“…22 Akay et al showed DBD coupled with Co/SiO 2 for Fischer−Tropsch synthesis. 23 In both cases, reactant conversions with plasma−catalyst combinations are higher than those with plasma alone or catalyst alone under tested conditions. Song et al placed DBD coupled with HZSM-5 downstream of polyethylene pyrolysis volatiles to generate aromatics-enriched oil and showed product yields are sensitive to plasma conditions.…”
Section: ■ Plasma Characterizationmentioning
confidence: 93%
“…The above sections revealed that a variety of supported nanocatalysts has been prepared by MW assisted methods. The supported nano catlaysts included simple metal catalysts such as Cu, [81][82][83]105,132 Ni, 105,118,136 Co, 105,119,120 Fe, 84 Ru, 85,86,[95][96][97][98][99]141 Ag, 112,116 Au, 112,129,131,142 Pt, [87][88][89][90][91][92]106,111,121,142,145,146 Ti, 122 Zr, 123 Pd, 93,[106][107][108]127,128,130,133,134,…”
Section: Catalysis By Supported Simple Metal Catalystsmentioning
confidence: 99%
“…Some authors even carried out the catalysis reactions under MW reaction conditions over supported nanocatalysts and found fairly good conversion and/or yield. 112,119,120,128,156 The better catalytic activity of MW synthesized supported nanocatalysts can be assumed to be due to improved homogeneous distribution of smaller nanocatalyst particles, larger volume to surface ratio, surface heterogeneity, synergistic interaction between metals as well as stronger interaction between nanocatalyst and support materials. The data on stability of MW synthesized nanocatalyst during recycle is hardly available and more investigation is needed in the area.…”
Section: Scope and Outlookmentioning
confidence: 99%
“…The selective heating of electrons in a nonthermal plasma generates significant populations of energetic species, enabling lowtemperature activation of stable molecules and alternative pathways to overcome thermodynamically unfavourable reactions [52,[57][58][59]. Incorporating catalyst materials into plasma reactors, known as plasma catalysis (PC), shows significant promise for activating stable molecules such as N 2 and CO 2 and converting them into valuable materials for use in agriculture, transport, and chemical synthesis [13,39,52,[56][57][58][59][60][61][62][63][64][65]. PC processes are attractive for remote applications [57] such as a Lunar or Martian settlement because they are modular and small [57,66], can be cycled rapidly [60,67], are compatible with intermittent power [9,66], and are operated at low temperatures and atmospheric pressure [9,12,13,52,68], eliminating the cost, size, and complexity associated with conventional thermochemical plant equipment.…”
Section: Plasma Processing and Catalysismentioning
confidence: 99%